EPITHERMAL AND MESOTHERMAL MINERALIZATION IN THE RUSSIAN NORTHEAST - Sidorov A.A. (My University, 2004)
Terranes of passive continental margins are most widespread among the Kolyma-Chukot group of terranes, whose accretion terminated in the Barremian-Aptian time. They include kilometer-scale sandy-shaly sequences deposited on the granitized Precambrian basement in the Permian-Late Jurassic. Analogous sequences are widespread in the sedimentary cover of the Omolon and Okhotsk cratonic terranes. These terrigenous rocks serve as the major medium for the accumulation of mesothermal and, to a lesser extent, epithermal deposits in the Russian Northeast.